INSILICO DOCKING STUDIES TO IDENTIFY POTENT INHIBITORS OF ALPHA-SYNUCLEIN AGGREGATION IN PARKINSON DISEASE - .L. JAYARAJ, RICHARD; Ranjani, V.; Manigandan, K.; Elangovan, Namasivayam (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Background: Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease. Etiology of PD is progressive loss of dopaminergic neurons in Substantia nigra pars compacta (SNpc). One of the pathological hallmarks of PD is the presence of intracellular proteinaceous substances termed ‘Lewy bodies' composed of aggregated alpha-synuclein which is responsible for its toxic effect on SNpc. Hence any therapeutic target which blocks α-synuclein aggregation will provide a new channel to cure PD. Objective: The aim of the present study is to identify potent inhibitors (ligands) which binds to active site of α-synuclein and prevents self-association. Methods: In this study, insilico molecular docking was done against α-synuclein using five plant derived compounds namely (a) stimovul (b) 7,8dihydroxycoumarin, (c) etorphine (d) propoxyphene and (e) pentazdine. These compounds were analyzed for their Lipinski and ADMET properties using Accelrys Discovery studio 3.5. Molecular docking was performed between ligand and protein using Lead IT. Results: Results revealed that the best fit ligands against active site of α-synuclein were identified as Stimovul with a docking score of -4.5122 and the interacting amino acids were found to be SER 87 and VAL 95 followed by other compounds. Conclusion: These compounds which have the ability to bind to α-Synuclein insilico can be further developed using invitro and in vivo studies as a potent anti-parkinson drug. Keywords: Parkinson disease, Substantia nigra, Molecular docking, Lipinski, ADMET.